Myth and Symbol in the Poems of Badr Shakir as-Sayyab and Sergei Alexandrovich Yesenin - Bahari, Hussein Ali Khudair; Ismaeel, Hadeel (Al-Adab Journal, 2021)
This paper tackles the issue of myth and symbol in the poems of Badr Shakir as-Sayyab and Sergei Alexandrovich Yesenin, and the effect of the surrounding world which is made apparent therein. The analysis has been made of the points of similarity in their poems, and how they had pictured the world as a whole via the exploitation of myth and symbol, where myth, the poetry of both, had the indication of love, freedom, life, hate, and injustice.